Sistem Pemesanan Produk pada PT. Talasi Weetabula Berbasis Web - Lidia Kartini Ina; Cecilia D. P. Binti Gabriel; Maria Wilda Malo (Pusat Riset dan Inovasi Nasional, 2025)
A decision support system (DSS) is a tool that helps decision makers choose the optimal option based on predetermined standards. In human resource management, determining the eligibility of ASN (State Civil Servants) employees to receive pensions is crucial because it has an impact on worker welfare, career prospects, and state budget management. This study suggests the use of the Multi-Attribute Decision Making (MADM) approach to build a decision support system for assessing the eligibility of ASN employee pensions. The MADM method is a decision-making process that produces the best choices by considering a number of criteria and options. Retirement age, length of service, work performance, health, and other variables related to the applicable pension policy are some of the criteria considered in this study to assess pension eligibility. The system methodology consists of a number of steps, including determining the criteria, assigning weights to each criterion, and assessing alternatives based on these criteria using computational methods such as TOPSIS (Technique for Order Preference by Samelight to Ideal Solution) and AHP (Analytical Hierarchy Process). The evaluation findings will provide advice on employee eligibility for retirement or ability to continue working. By offering transparent and objective analysis, the developed technology is expected to direct the ASN employee retirement decision-making process and ensure that the decision-making is more accurate and in accordance with related regulations. Therefore, this approach can improve the effectiveness and efficiency of human resource management in government agencies.